Effect of a sanitation cut on radial growth in Pinus hartwegii forest - Rojas-García, Fabiola; Gómez-Guerrero, Armando; Endara-Agramont, Ángel Rolando; Gutiérrez García, Genaro; Reyes Hernández, Valentín José; Ángeles Pérez, Gregorio; de Jong, Bernardus H.J. (Instituto de Ecología, A.C., 2022)
Pinus hartwegii forests are susceptible to the attack of forest pests, so sanitation interventions in the stands of this species must be analyzed. The objective of this work was to evaluate the effects of sanitation cuts on the radial growth of residual trees, in monospecific stands of P. hartwegii of the Área de Protección de Flora y Fauna Nevado de Toluca. Ten measuring sites of remnant trees and stumps were established in stands operated during 2016 (1000 m2) in the West and East slopes of the volcano. The period 2013-2015 was considered as prior to sanitation, and 2016-2018 as after sanitation. The distribution pattern, horizontal and vertical structure were analyzed. Two density indices and two proficiency indices were calculated. Wood cores were collected in all individuals and the widths of the growth rings were measured by dendrochronological techniques. Growth was standardized by series of basal area increment (IAB). The growth of the remaining trees located on the periphery of the stumps was significantly different between the exposures. The BAI increased 37.3% after sanitation in the West exposure, while in the East exposure the BAI increased 61.6%. The remaining trees located between 2.5 and 5 m with respect to the stump had higher BAI in both exposures. Pinus hartwegii forests respond positively to sanitation cuts with a statistically significant increase in IAB.